PENYELESAIAN SENGKETA KONSUMEN AKIBAT KERUGIAN KARENA TIDAK TERPENUHINYA HAK-HAK KONSUMEN ATAS INFORMASI YANG BENAR DALAM RAHASIA DAGANG - Fitriah, Fitriah (Solusi, 2018)
The purpose of doing business is to achieve maximum profit so that business actors try to win the competition even though it is done through ways that are contrary to ethics and law so that not only other business actors are harmed but also consumers. Trade Secret that is part of the Right of Wealth Intellectual property is an exclusive right for the owner or recipient of the right to enjoy the economic benefits of information that is not publicly known in the field of technology and business. The owner of the Trade Secret as an entrepreneur has the right to conceal the information of such economic value to anyone including the consumer. But on the other hand under the Consumer Protection Act (UUPK), the consumer has the right to correct information on the goods it receives. The settlement of the dispute due to the non-fulfillment of the consumer right on the correct information about the goods may occur due to two possibilities, namely: with consumers who violate UURD for seeking the correct information about the product of the goods it receives by committing an act against the law. And disputes related to business actors who violate UUPK because they do not provide the correct information about the goods being produced and marketed. In the case of a dispute due to a business actor who does not provide correct information about the goods produced and marketed, in accordancewith UUPK, any consumer or aggrieved consumer group may by suing a businessactor through an agency in charge of resolving disputes between consumers andbusiness actors.